PARTISIPASI MASYARAKAT PADA PILKADA SERENTAK DI MASA PANDEMI COVID 19 (STUDI KASUS PILKADA KABUPATEN INDRAGIRI HULU) - Dimas Zulfitrah; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Throughout 2020, Indonesia faced the Covid-19 pandemic which made all life orders undergo very significant changes, including the political field. The government remains adamant about holding regional elections on December 9 when the Corona outbreak has not subsided. This has reaped pros and cons among political elites and observers. Political participation is the activity of citizens who act as individuals intended to influence decision-making by the government, since participation can be individual or collective, organized or spontaneous, steady or sporadic, peacefully or violently, legally or illegally, effectively or ineffectively. This research uses a qualitative research type method, namely a research procedure that produces descriptive data. As for the descriptive data in question, it is speech or writing and the observable behavior of the person (the subject himself). In qualitative research, no numbers were found that were analyzed using statistical tools, but rather data were obtained from descriptive research. Descriptive means used to reveal an empirical fact objectively scientifically based on the logic of the author's scientific discipline, namely Government Science. The results showed that in Indragiri Hulu Regency, the participation rate increased with the number of voters193,299 people with a ratio of 66.73% compared to the previous period of regional elections. The supporting factor for the increase in the level of community participation in the regional elections in Indragiri Hulu Regency during the Covid-19 pandemic refers to the theory of the awareness of the People of Indragiri Hulu in carrying out their obligations as a society, then the diverse political situation can be seen from the large number of election participants who have various professional backgrounds so as to reach various groups. Next is campaign activities as a targeted participation stimulant with various restrictions and rules from election organizers. Keywords : Regional Elections, Participation, Covid 19